1998
DOI: 10.1007/bf03350323
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypervitaminosis D3 determines a decrease in C-cell numbers and calcitonin levels in rats

Abstract: Many papers have reported that chronic hypercalcemia induced either by large doses of vitamin D or by the administration of calcium or parathormone, produces hypertrophy and hyperplasia of C cells. However, more recent studies suggest that the effect of elevated calcium or 1.25(OH)2D3 concentration on the production of calcitonin may be more complex than previously suspected. To assess the validity of such a response an experimental model, where hypercalcemia was induced with vitamin D3 overdose, was designed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
3
1
Order By: Relevance
“…Nor could we confirm the ability of C cell growth at various concentrations of free Ca 2+ in this study. These results together confirm that C cell regeneration is complex, being regulated not only by free Ca 2+ , but also by other physiological factors, such as vitamin D 3 , biogenic amines and polypeptide hormones (Murray 1991;Sawicki 1995;Tiegs et al 1986;Martin-Lacave et al 1998).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nor could we confirm the ability of C cell growth at various concentrations of free Ca 2+ in this study. These results together confirm that C cell regeneration is complex, being regulated not only by free Ca 2+ , but also by other physiological factors, such as vitamin D 3 , biogenic amines and polypeptide hormones (Murray 1991;Sawicki 1995;Tiegs et al 1986;Martin-Lacave et al 1998).…”
Section: Discussionsupporting
confidence: 80%
“…B At 7 and 28 days in culture, C cell number is the highest at 0.78 mM of free Ca 2+ , although there is no statistically significant difference between the paired values at the indicated ranges of free Ca 2+ concentration of free Ca 2+ may bring about C cell hyperplasia, which occurs in some experimental animal models (Zabel 1976). However, our study did not reproduce this result, lending support to the results of other studies that hypercalcemia fails to induce C cell hyperplasia (Tiegs et al 1986;Martin-Lacave et al 1998). The concentration of 0.78 mM free Ca 2+ increased the number of C cells, but there was no statistically significant difference between the various concentrations of free Ca 2+ used in our study.…”
Section: Discussionsupporting
confidence: 45%
“…However, Martin-Lacave et al (1998) did not detect such changes affecting C cells in a hypercalcemic state.…”
Section: Introductioncontrasting
confidence: 49%
“…On the contrary, Martin-Lacave et al (1998) concluded that rat C cells do not respond with hypertrophic and hyperplastic changes nor are there significant alterations in serum CT levels in the hypercalcemic state. The recent data of Toda et al (2003) also suggest that various free Ca concentrations reaching porcine thyroid C cells in culture did not change their number significantly, i.e.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation